The Effect of Oral Methadone on the QTc Interval in Advanced Cancer Patients: A Prospective Pilot Study - Reddy, Suresh (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Recent reports suggest that high doses of methadone may prolong QTc interval and occasionally cause torsades de pointes; however, few of these studies involved the palliative care population. OBJECTIVE: The purpose of this study was to determine the effect of initiation of methadone on QTc interval in patients with cancer pain seen at the palliative care setting. METHODS: We enrolled 100 patients with cancer in this prospective study. Patients were followed clinically and electrocardiographically for QTc changes at baseline, 2, 4, and 8 weeks. Contributing factors for QTc prolongation such as medications, cardiovascular diseases, and electrolytes disturbances were documented. QTc prolongation was defined as greater than 430 ms in males and greater than 450 ms in females, and significant QTc prolongation was defined as QTc interval greater than 25% increase from baseline or 500 ms or more. RESULTS: Electrocardiographic (ECG) assessments were available for 100, 64, 41, and 27 patients at baseline, 2-, 4-, and 8-week follow-up, respectively. At baseline prior to initiation of methadone, 28 (28%) patients had QTc prolongation. Clinically significant increase in QTc occurred in only 1 of 64 (1.6%) patients at week 2, and none at weeks 4 and 8. There was no clinical evidence of torsades de pointes, ventricular fibrillation, or sudden death. QTc prolongation was more frequent among patients with increased baseline QTc interval. CONCLUSIONS: Baseline QTc prolongation was common, whereas significant QTc interval 500 ms or more after methadone initiation rarely occurred, with no evidence of clinically significant arrhythmias. This study supports the safety of methadone use for pain control in patients with advanced cancer in the palliative care setting.